PROGRAM PENCEGAHAN PERNIKAHAN USIA DINI (PRO HANDINI) BERBASIS INTERDISIPLIN DI SMP MUHAMMADIYAH 7 YOGYAKARTA - Suryaningsih, Endang Koni; Tunggali, Ade Putra; Khoiryasdien, Andhita Dyorita; Aryudaningrum, Nastiti (LPPM Universitas Bina Bangsa, 2025)
The high rate of early marriages in Yogyakarta is partly driven by unplanned pregnancies (Kehamilan Tidak Diinginkan/KTD). KTD is influenced by several factors, including a lack of adolescent knowledge about reproductive health and environmental influences that shape attitudes, mindsets, and behaviors regarding adolescent sexuality. This Community Service Programme (PKM) aligns with government initiatives aimed at reducing and preventing early marriages, starting within educational settings. The programme's goal is to establish the Youth Reproductive Health Information Centre (PIKR-R) at SMP Muhammadiyah 7 Yogyakarta as a preventive measure against early marriages, while also enhancing students' knowledge of adolescent reproductive health. The focus of this PKM is the implementation of Health Technology Assessment through the establishment of the Youth Reproductive Health Information Centre, with the aim of preventing early marriages at SMP Muhammadiyah 7 Yogyakarta. Students from various professional backgrounds, including Midwifery, Psychology, and Communication Science, will be involved in the programme. This initiative supports three out of the eight Key Performance Indicators (KPIs) for Higher Education Institutions, including enabling lecturers to engage in off-campus activities, providing students with off-campus experiences, and applying research outcomes for community benefit, particularly at SMP Muhammadiyah 7 Yogyakarta.